Children's Culture Shock in the Multilingual Family - Nadya Karina Arimbi (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2020)
This article is a study about the phenomenon of children culture shock in countries all over the world. It talks about the symptoms of culture shock, the problem that might be in concern by children whose parents have a different cultural background. The goal is to show a problem that might be in concern by children who have a different cultural background, the sources of the problem, and the strategies that parents apply to minimize children's culture shock. Parents in the multilingual family background from around the world are chosen randomly as the subjects. By using method Netnography written language and is expected to provide a valid data. The result, showed that nowadays, parents are a worry to push their children to learn more than one language, and they are afraid it would make children got stuck in the symptoms of culture shock. By that fact parents’ improper education and society to raising multilingualism are be one of the weapons for children who face culture shock. To reduce the impact of culture shock, ‘one person-one language’ could become an option to heal multilingual children from culture shock. In sum, this is a mixed marriage family, who has different native language and cultural backgrounds, but is eager to have multilingual children, or for parents who fear their children will experience delayed speech because they learn more than a language at a young age.